The Power of Digital Signature Evidence in Indonesian Civil Procedural Law - Reza Kautsar Kusumahpraja (LOCUS MEDIA PUBLISHING, 2022)
Enforcement of civil law is carried out through civil procedural law in order to provide justice for the parties to the litigation in order to make light of the case which was carried out in the evidentiary trial. Evidence is regulated in Article 164 HIR/284 Rbg. Nowadays the development of evidence has expanded so that electronic evidence appears after the enactment of Law Number 11 of 2008 concerning Information and Electronic Transactions, one of which is an electronic signature (digital signature). The problem that arises is how strong is the evidence in civil procedural law in Indonesia? So the purpose of this study is to determine the strength of evidence of electronic signatures in Indonesian civil procedural law. This study uses a normative type of research with a legal and conceptual research approach which is then analyzed deductively in order to produce legal arguments in a systematic, logical and theoretical manner. The results of this study found that the strength of evidence against electronic signatures differed depending on the type of electronic signature presented at the trial.